Relationship between Abnormal Lipid Metabolism and Gallstone Formation - Xiang Li; Xiaodan Yin; Jun Xu; Lei Geng; Zhengtao Liu (The Korean Journal of Gastroenterology)
Cholelithiasis is a common biliary system disease with a high incidence worldwide. Abnormal lipid metabolism has been shown to play a key role in the mechanism of gallstones. Therefore, recent research literature on the genes, proteins, and molecular substances involved in lipid metabolism during the pathogenesis of gallstones has been conducted. This study aimed to determine the role of lipid metabolism in the pathogenesis of gallstones and provide insights for future studies using previous research in genomics, metabolomics, transcriptomics, and other fields.